The knowledge of emergency contraception and dispensing practices of Patent Medicine vendors in South West Nigeria (2010)
Patent Medicine Vendors (PMVs) can play a critical role in increasing access to emergency contraceptive pills (ECPs) in developing countries, but few studies have examined their knowledge and dispensing practices. Using cluster sampling, the authors selected and interviewed 97 PMVs (60.8 per cent female) in Oyo and Ogun States of Nigeria to assess their knowledge, dispensing practices, and referral for ECPs. About one-third (27.8 per cent) of respondents were not aware of ECPs, and only half knew that ECPs could prevent pregnancy. Forty per cent had ever dispensed ECPs. Reasons proffered by those who do not dispense ECPs included barriers from the State Ministry of Health, police, other regulatory agencies, and religious beliefs. Only 50.5 per cent have referral arrangements for clients. Strategies to increase access to ECPs through PMVs include training on counseling techniques and referral, effective government regulation, and community involvement. Where unsafe abortion is a major cause of maternal mortality, these strategies offer protection for many women in the future.